PERAN GURU DALAM PELESTARIAN BAHASA JAWA DI KALANGAN SISWA PERI-URBAN SDN JATISARI KOTA SEMARANG - Diah Khoirunnafiah; Nia A’isyah Septiarini, Nindhita Pradiningtyas; Kayla Nafiisa Sugiono, Deni Setiawan (STKIP Subang, 2025)
This study presents the role of the teachers in preserving Javanese language at SD Jatisari, a peri-urban area. The importance of Javanese language preservation in the midst of modernization and the dynamics of language use in peri-urban areas motivates this research. The purposes of this research are to identify the teacher's role in preserving Javanese language and to analyze the factors that influence these efforts. The research employed a descriptive qualitative method with a case study approach. The subjects of this study were teachers and students with a total 20 teachers and 468 students who were taken using purposive sampling. The sample involved homeroom teachers with the criteria of being active, experienced in guiding students, and communicative. While the criteria for students are gifted and outstanding students. Data were collected through interviews, observations, and documentation, and then validated by source triangulation. The results show that the teacher's role is realized in Javanese language learning, extracurricular activities, competitions, and the use of Javanese language in school communication. Supporting factors include teacher support, student participation, a flexible curriculum and the availability of adequate facilities and infrasturcture. Local language preservation is possible, even in areas exposed to modernization. Practices such as those at SDN Jatisari can serve as a good example for other schools in peri-urban areas in their efforts to preserve their mother tongue.